2005
DOI: 10.1007/s10593-005-0116-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic routes towards tetrazolium and triazolium dinitromethylides

Abstract: probably via dinitromethylide followed by cyclization and loss of nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The latter observation led to the conclusion that water was involved in a stage that limited the hydrolysis rate. Further analysis of the results indicated that two mechanisms of the hydrolysis with observed rate constants k 1 ] was proposed. According to the proposal the active complex decomposed rapidly into nitroimidazole 7, nitric(V) acid, and water.…”
Section: -Denitration Of Dinitroimidazoles 1-4mentioning
confidence: 99%
See 3 more Smart Citations
“…The latter observation led to the conclusion that water was involved in a stage that limited the hydrolysis rate. Further analysis of the results indicated that two mechanisms of the hydrolysis with observed rate constants k 1 ] was proposed. According to the proposal the active complex decomposed rapidly into nitroimidazole 7, nitric(V) acid, and water.…”
Section: -Denitration Of Dinitroimidazoles 1-4mentioning
confidence: 99%
“…48 The products served as starting materials in syntheses of adenines. Two other compounds, the (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) N)adenine and (1-3 H)ribose, were also prepared. The compounds were then enzymatically coupled to isotopically modified ribosyl groups to give respectively substituted adenosines (31, Figure 5).…”
Section: Nucleophilic Cine-substitutionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Its various salts and N-methyl derivatives were prepared from 5-dinitromethyltetrazole (1), 5,6 and the monosodium salt of 1 was also from FOX-7. 7 In the synthesis of tetrazoles containing dinitromethyl moiety, trinitroacetonitrile has been mainly employed. 5,6 Due to easy decomposition, trinitroacetonitrile should be handled with utmost care, and kept in solution.…”
mentioning
confidence: 99%